2014
DOI: 10.1007/s11738-014-1661-2
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous hydrogen peroxide enhanced the thermotolerance of Festuca arundinacea and Lolium perenne by increasing the antioxidative capacity

Abstract: Heat stress is one of the most detrimental environment stresses for plants. Hydrogen peroxide (H 2 O 2 ) is produced quickly in response to various stresses and likely plays a positive role in transmitting stress signal in organisms. This investigation addressed whether an exogenous H 2 O 2 application would affect the heat response of turfgrasses and induce acclimation. Tall fescue (Festuca arundinacea cv. Barlexas) and perennial ryegrass (Lolium perenne cv. Accent), two important cool-season turfgrasses and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 44 publications
(50 reference statements)
2
33
1
1
Order By: Relevance
“…5) was lower than in non-grafted plants, although the production of H 2 O 2 was increased (Fig. 6) in the leaves of grafted -Cd/?Cd plants, suggesting a regulatory role of ROS in the cross talks of stress signaling and redox metabolic signals (Golldack et al 2014;Wang et al 2014), which can be related to a quick response to the stress from rootstocks to scions of these grafted plants. Moreover, rootstocks of grafted ?Cd/-Cd showed increased MDA content when compared with rootstocks of selfgrafted -Cd/-Cd plants, which could also indicate stress signaling from scions to rootstocks.…”
Section: Discussionmentioning
confidence: 84%
“…5) was lower than in non-grafted plants, although the production of H 2 O 2 was increased (Fig. 6) in the leaves of grafted -Cd/?Cd plants, suggesting a regulatory role of ROS in the cross talks of stress signaling and redox metabolic signals (Golldack et al 2014;Wang et al 2014), which can be related to a quick response to the stress from rootstocks to scions of these grafted plants. Moreover, rootstocks of grafted ?Cd/-Cd showed increased MDA content when compared with rootstocks of selfgrafted -Cd/-Cd plants, which could also indicate stress signaling from scions to rootstocks.…”
Section: Discussionmentioning
confidence: 84%
“…High levels of H 2 O 2 generated during abiotic stress, including drought stress, can damage cellular structures but a low concentration of H 2 O 2 is maintained within the cells and functions as a signal, mediator or effector involved in developmental processes and stress responses [22] [30]. High levels of H 2 O 2 can by itself result in oxidative damage to the cells [21] but it has been demonstrated in a number of plants species, including maize [31], mustard [32], tall fescue and rye grass [33], that an increase in H 2 O 2 levels primes the plants for enhanced drought stress resistance. Significant increases in H 2 O 2 levels in 10 and 100 nM ES-treated Arabidopsis subjected to drought conditions were responses to drought stress and not to the ES treatment and it indicates that H 2 O 2 contributed to the enhanced drought stress tolerance of these plants.…”
Section: Effects Of 17β-estradiol Application On Stress-related Biochmentioning
confidence: 99%
“…Recent studies have shown that priming can also modulate abiotic stress tolerance (Filippou et al, 2012; Hossain and Fujita, 2013; Mostofa and Fujita, 2013; Borges et al, 2014; Mostofa et al, 2014a,b,c; Nahar et al, 2014; Wang et al, 2014a). Despite the agronomic and ecological importance of priming, in-depth molecular mechanisms associated with priming in plants are still unknown (Conrath, 2011).…”
Section: Introductionmentioning
confidence: 99%